Taxonomic notes on the genus Baetiella Uéno from China, with the descriptions of three new species (Ephemeroptera: Baetidae) - Shi, Weifang; Tong, Xiaoli (Zootaxa, 2015)
Nine Baetiella species, including three new species, are reported from China. Baetiella lanpingensis n. sp. is diagnosed by the 2nd segment of labial palpus without inner-apical lobe, the posteromedian margin of terga I–VI each with a single protuberance, posterior margin of sterna V–IX each with a row of continuous long spatulate setae and median caudal filament with only one segment. Baetiella sexta n. sp. is characterized by the 2nd segment of labial palpus bearing an inner-apical lobe, the posteromedian margins of terga I–VI each with a single protuberance, posterior margins of sterna I–VII smooth and median caudal filament with 3–5 segments. Baetiella spathae n. sp. is distinguished from its congeners by the terminal segment of labial palpus asymmetric coniform, the posteromedian margin of terga I–IX each with a single protuberance and posterior margin of sterna V–IX each with a row of long spatulate setae. Additionally, B. macani (Müller-Liebenau, 1985) is removed from the synonymy with B. bispinosa (Gose, 1980) and considered as a valid species. B. marginata Braasch, 1983 is recorded for the first time from China. A key to fourteen species of Baetiella known from mature nymphal stages in the world is provided.